2012
DOI: 10.1371/journal.pone.0051875
|View full text |Cite
|
Sign up to set email alerts
|

CSP—A Model for In Vivo Presentation of Plasmodium berghei Sporozoite Antigens by Hepatocytes

Abstract: One target of protective immunity against the Plasmodium liver stage in BALB/c mice is represented by the circumsporozoite protein (CSP), and mainly involves its recognition by IFN-γ producing specific CD8+T-cells. In a previous in vitro study we showed that primary hepatocytes from BALB/c mice process Plasmodium berghei (Pb) CSP (PbCSP) and present CSP-derived peptides to specific H-2kd restricted CD8+T-cells with subsequent killing of the presenting cells. We now extend these observations to an in vivo infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Some of these molecules are polarized toward the basolateral surface of the hepatocyte, thereby maximizing the potential for lymphocyte interaction and activation 15 . Furthermore, both in vitro and in vivo evidence indicates that hepatocytes can present antigen to naive T cells [35][36][37][38] . Electron microscopy has revealed that hepatocytes and naive T cells physically interact in an ICAM-1-dependent and MHC-dependent fashion 15 .…”
Section: Hepatocytesmentioning
confidence: 99%
“…Some of these molecules are polarized toward the basolateral surface of the hepatocyte, thereby maximizing the potential for lymphocyte interaction and activation 15 . Furthermore, both in vitro and in vivo evidence indicates that hepatocytes can present antigen to naive T cells [35][36][37][38] . Electron microscopy has revealed that hepatocytes and naive T cells physically interact in an ICAM-1-dependent and MHC-dependent fashion 15 .…”
Section: Hepatocytesmentioning
confidence: 99%
“…CSP coats the sporozoite surface, is shed from the motile sporozoite (9), and is transported to the hepatocyte cytoplasm (10). CSP is a target of protective class I-dependent CTL responses (10)(11)(12). Depending on the mouse model, CSP can also elicit important CD4 + T-cell responses (13,14) and MHC class IIdependent IgG responses (15).…”
mentioning
confidence: 99%
“…Depending on the mouse model, CSP can also elicit important CD4 + T-cell responses (13,14) and MHC class IIdependent IgG responses (15). In some systems, large numbers of adoptively transferred CSP-specific T-cell clones or endogenously generated CTLs can protect mice against sporozoite challenge (8,12,14,16,17). However, it remains unclear whether CSP-specific CTLs in naïve subjects can be primed to achieve protection with existing vaccination approaches.…”
mentioning
confidence: 99%
“…In support of the former notion, it has been proposed that hepatocytes only present antigens that are secreted into the cytoplasm after invasion or during cell traversal (29, 30). Recent genome-wide immune profiling approaches in the two murine models provided evidence for each of these propositions (22, 31).…”
Section: Introductionmentioning
confidence: 97%